Pengaruh Motivasi Kerja dan Kompensasi Terhadap Kinerja di PT Semesta Multi Sekurindo - Rani Riffani; Nina Nurani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Motivation and compensation are phenomena that can affect a company. This study aims to find out both the partial and simultaneous effects with the research title 'The Influence of Motivation and Compensation on the Performance of Security Employees at PT. Semesta Multi Sekurindo.' This study uses a descriptive and verification method with a quantitative approach, using surveys and questionnaires as data collection instruments. The sampling technique uses random sampling with the Slovin formula, consisting of 122 respondents. Data analysis is done using multiple linear regression techniques to assess the influence of independent variables on the dependent variable. The research results show that, partially, work motivation has a positive and significant effect on the performance of security employees. Partially, work compensation also has a positive and significant effect on the performance of security employees. Work motivation and work compensation together have a positive and significant effect on the performance of security employees at PT. Semesta Multi Sekurindo (PT.SMS). These research findings imply that work motivation and compensation affect the performance of security employees, with an emphasis on the need to further improve opportunities for self-development, performance-based incentive systems, and employee independence at work so that performance can continue to improve for a fair company balance.